Implementation of Fingerprint Biometrics on Smart Door Entrance Access Integrated with Internet of Things-based PINs - Handini, Wulan Tri; Endri, Jon; Salamah, Irma (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Security is something that must often be ignored by most people and think it is safe, but it turns out that someone can still lose their valuables. In this final project, we will design an Internet of Things (IoT)-based smart door access tool that uses a fingerprint and pin password using the Optical Scanner Sensor method. The purpose of making and designing a smart door tool based on the Internet of Things (IoT) is one of them to apply the optical method as a method used to recognize fingerprint biometric identification. By using a smartphone (android) as a controller using the NodeMCU contained in the ESP2866 WiFi module via an internet connection connected to an application made with MIT App Inventor. In the application of fingerprint sensors using the optical method, the scanning process is obtained through finger scanning based on the effect of light reflection that occurs on the optical sensor on the fingerprint. So as to produce digital image retrieval on identified fingerprints. The communication that uses the fingerprint sensor and Arduino uno as a data processing unit uses serial data communication. When the command has run according to its function, the results of the data obtained enter in realtime at the data processing place.